El Archivo de la Palabra de Radio Nacional de España - Ariza Chicharro, Rosa María (Revista General de Información y Documentación, 2004)
RNE’s Word Archive constitutes the largest archive of non musical sound recordings in Spain and one of the most outstanding in Europe. It gathers different types of recordings proceeding from the programming of its broadcasting stations, as well as from a variety of sources used in the elaboration of broadcasts. Some of the issues addressed in this work are: origin and evolution of the archive; growth, composition, classification, origin and characteristics of its material supports, and the peculiar characteristics encountered in the documental process throughout the selection, registering and analysis of the recordings. The latest trends in the reproduction and preservation of sound are also discussed: the digitalisation of analogical recordings and their conversion into computer accessible audio files. There is also discussion of the repercussions of these technological conversions in the management of archival sources, as well as a description of the digital sound archive.